Enhancing Market Competitiveness of Food MSMEs through Halal Certification - Dedy Sukmana (Dinasti International Journal of Digital Business Management, 2026)
This study examines the role of halal certification in enhancing the competitiveness of food Micro, Small, and Medium Enterprises (MSMEs) by integrating market signaling and capability development perspectives. Using a quantitative cross-sectional design, primary data were collected from food MSMEs in Indonesia through a structured survey. Partial least squares structural equation modeling (PLS-SEM) was employed to analyze the direct and indirect effects of halal certification on firm-level competitiveness, with operational capabilities modeled as a mediating variable. The results indicate that halal certification has a positive and statistically significant effect on food MSME competitiveness. In addition, halal certification is found to significantly strengthen internal operational capabilities, including process standardization, hygiene and sanitation management, ingredient traceability, employee training, and documentation practices. These operational capabilities, in turn, have a strong positive effect on competitiveness. Mediation analysis confirms that operational capabilities partially mediate the relationship between halal certification and competitiveness, indicating that halal certification enhances competitiveness both directly, through market signaling and increased consumer trust, and indirectly, through internal capability development. The findings contribute to the literature by demonstrating that halal certification functions not only as a religious or regulatory compliance mechanism but also as a strategic tool for organizational upgrading and sustainable competitive advantage. By integrating signaling theory and the resource-based view, this study provides a more comprehensive understanding of the mechanisms through which certification-based standards influence food MSME performance. From a policy and managerial perspective, the results suggest that halal certification support programs should emphasize both administrative facilitation and capability-building interventions to maximize the competitiveness benefits for food MSMEs.